2018
DOI: 10.1177/1403494818765705
|View full text |Cite
|
Sign up to set email alerts
|

Time to dismiss the idea of a structural fix within government? An analysis of intersectoral action for health in Danish municipalities

Abstract: It is time to dismiss the idea that intersectoral action for health can be achieved by means of a structural fix. Rather than rearranging organizational boundaries it may be more useful to seek to manage the silos which exist in any organization, e.g. by promoting awareness of their implications for public health action and by enhancing the boundary spanning skills of public health officers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(49 citation statements)
references
References 26 publications
1
47
0
1
Order By: Relevance
“…The achievement of testing the designed collaborative intervention elements seemed to be highly dependent on timing within each unit, on unpredictable internal issues between the three units, and the stakeholders' lack of mandate to "get things done" in another unit. These contextual features are in line with earlier research, showing that, while intersectoral committees without formal authority in other departments may generate ideas, they lack the capacity to ensure implementation [35]. This specific feature of the organizational context of the stakeholders may have been overlooked, as the stakeholders were seen as co-designers in the partnership and not as a genuine target group per se.…”
Section: The (Overlooked) Social Contexts Of the Projectsupporting
confidence: 81%
“…The achievement of testing the designed collaborative intervention elements seemed to be highly dependent on timing within each unit, on unpredictable internal issues between the three units, and the stakeholders' lack of mandate to "get things done" in another unit. These contextual features are in line with earlier research, showing that, while intersectoral committees without formal authority in other departments may generate ideas, they lack the capacity to ensure implementation [35]. This specific feature of the organizational context of the stakeholders may have been overlooked, as the stakeholders were seen as co-designers in the partnership and not as a genuine target group per se.…”
Section: The (Overlooked) Social Contexts Of the Projectsupporting
confidence: 81%
“…Por otro lado, la histórica tendencia natural al trabajo en silos supone una clara barrera; además, los sectores de los gobiernos locales tienen una estructura muy verticalizada, con sus propios directores, presupuestos, objetivos, resultados, lenguaje y tecnicismos 10 .…”
Section: A H E a D O F P R I N Tunclassified
“…However, while it is often believed that bringing policy teams or specialized groups to ‘the center’ of government can provide the uptake and integration of health concerns across government, a recent study 3 among Danish municipalities found that the organization of public health teams (employing public health coordinators) in central units, did not strengthen their coordination and oversight role or imbue them with the authority to change policy and practice across the diverse portfolios of local government as was assumed. Instead, the public health officers’ problems with gaining traction among non-health departments were mostly reproduced.…”
Section: The Public Health Coordinatorsmentioning
confidence: 99%
“…While different ways of organizing public health held different advantages and disadvantages, most municipalities had not managed to solve the overall problem of establishing more widespread and profound intersectoral commitment and decision-making for health. 3 Thus, placing public health coordinators in the central CEO office may not necessarily provide the institutional power needed to affect the agenda of local policy-making. This is also supported by Scheele et al 4 who found that no Scandinavian municipality has been fully successful in terms of organizing and establishing governance for health equity.…”
Section: The Public Health Coordinatorsmentioning
confidence: 99%
See 1 more Smart Citation